"Clinicopathological features and treatment outcomes of differentiated thyroid cancer in Saudi children and adults". Issue 1 (December 2015) - AL-Qahtani, Khalid; Tunio, Mutahir; Al Asiri, Mushabbab; Aljohani, Naji; Bayoumi, Yasser; Riaz, Khalid; AlShakweer, Wafa
Abstract Introduction Age is an important prognostic factor in differentiated thyroid cancer (DTC). Our aim was to evaluate differences in clinicopathological features and treatment outcomes among children and adult patients with DTC. Materials and methods We studied 27 children (below 18 years) with DTC treated during the period 2000–2012 and were compared with (a) 78 adults aged 19–25 years and (b) 52 adults aged 26–30 years treated during the same period in terms of their clinicopathological features and long term treatment outcomes. Locoregional recurrence (LRR), locoregional control (LRC), distant metastasis (DM), distant metastasis control (DMC), disease free survival (DFS) and overall survival (OS) rates were evaluated. Results Mean age of children was 13.5 years (range: 5–18), while mean age of adults was 24.6 years (range: 19–30). In children, female: male ratio was 2.85:1, and in adults female: male ratio was 7.1:1 (P = 0.041 ). No significant difference in tumor size was seen between the two groups (P = 0.653 ). According to American Thyroid Association (ATA) risk stratification classification, the children (85.2 %) were found to have at high risk as compared to adultsP = 0.001 . Post-thyroidectomy complications and RAI induced toxicities were observed more in children than adults (P = 0.043 andP = 0.041 respectively). LRR occurred in 6 (22.2 %), 9 (11.5 %) and 3 (5.8 %) in age groups of <18 years, 19–25 years and 26–30 years respectively (P = 0.032) ; while DM was seen in 10 (37.0 %), 9 (10.3 %) and 5 (9.6 %) in age groups of <18 years, 19–25 years and 26–30 years respectively (P = 0.002) . Ten year DFS rates were 67.3 % in age group below 18 years, 82.4 % in age group of 19–25 years and 90.1 % in age group of 26–30 years (P = 0.021) . Conclusion At the time of diagnosis, children with DTC were found to have more aggressive clinicopathological characteristics. Comparatively lower LRC, DMC and DFS rates in children warrants further multi-institutional studies.